Characterization of the complete chloroplast genome of Plumeria rubra cv. Acutifolia (Apocynaceae). Issue 1 (2nd January 2020) - Wang, Dong-Lan; Liu, Ying-Ying; Tian, Dan; Yu, Li-Ying; Gui, Ling-Jian
Abstract: Plumeria rubra cv. Acutifolia is a widely planted landscape tree in the subtropics. In this study, the complete chloroplast genome of P. rubra cv. Acutifolia was determined through Illumina sequencing method. The complete chloroplast genome has a length of 153, 912 bp, containing a small single-copy region (18, 036 bp), a large single-copy region (84, 852 bp), and a pair of IR regions (25, 512 bp). The chloroplast genome possesses 130 genes, including 85 CDS, 37 tRNA genes and 8 rRNA genes.  P. rubra cv. Acutifolia exhibited the closest relationship with P. cubensis in phylogenetic analysis.